2014
DOI: 10.1371/journal.pone.0108150
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Health System Barriers and Enablers for Antiretroviral Therapy (ART) for HIV-Infected Pregnant and Postpartum Women

Abstract: BackgroundDespite global progress in the fight to reduce maternal mortality, HIV-related maternal deaths remain persistently high, particularly in much of Africa. Lifelong antiretroviral therapy (ART) appears to be the most effective way to prevent these deaths, but the rates of three key outcomes—ART initiation, retention in care, and long-term ART adherence—remain low. This systematic review synthesized evidence on health systems factors affecting these outcomes in pregnant and postpartum women living with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 47 publications
4
92
0
4
Order By: Relevance
“…4,5 However, these studies show that the uptake of ART among HIV-positive pregnant women in sub-Saharan Africa remains a challenge and is associated with a shortage of healthcare workers, the poor attitudes of healthcare workers, transport costs and long waiting times. 15 In the present study, HIV-positive mothers on ART or ARV prophylaxis and HIVnegative mothers had a lower risk of premature birth compared with HIV-positive mothers not on ART or ARV prophylaxis.…”
Section: Discussionmentioning
confidence: 43%
“…4,5 However, these studies show that the uptake of ART among HIV-positive pregnant women in sub-Saharan Africa remains a challenge and is associated with a shortage of healthcare workers, the poor attitudes of healthcare workers, transport costs and long waiting times. 15 In the present study, HIV-positive mothers on ART or ARV prophylaxis and HIVnegative mothers had a lower risk of premature birth compared with HIV-positive mothers not on ART or ARV prophylaxis.…”
Section: Discussionmentioning
confidence: 43%
“…[16,31,32] We found that postpartum non-adherence until six months after delivery was associated with higher travel costs. Previous research similarly identified structural barriers such as long travel distance to the health facility, often linked with higher travel expenses.…”
Section: Discussionmentioning
confidence: 99%
“…Existing data shows that women who are ineligible for lifetime treatment and/or have a higher CD4 count may be more likely to fall out of care during the postpartum period [40,41]. The prevailing view that PMTCT is not for the mother [33,45] may contribute to this phenomenon.…”
Section: Gaps and Recommendationsmentioning
confidence: 99%